THE USE OF ARCHAIC WORDS IN THE NOVEL "AGABIY" BY K. KARIMOV - Atabayeva Gozzal (American Journals, 2023)
This article deals with archaic words in the novel "Agabiy" by the Karakalpak writer K. Karimov.
Keywords: vocabulary, artistic language